Robert Ludlum's the Bourne Vendetta: Jason Bourne #20 - Freeman, Brian, 1963-; Ludlum, Robert, 1927-2001 (New York : G.P. Putnam's Sons, 2025)
"A love from Bourne's past seeks his help when assassins threaten her husband, but only treachery burns hotter than true love in the New York Times bestselling series. Two years ago, Bourne knew he had to let Abbey Laurent walk away from his dangerous world. Now Abbey is back - and she's married to a top government official. But she's convinced someone is trying to kill her husband, and she wants Jason's help. Bourne follows the plot against this man into a deadly web of conspiracy that puts them all at risk. But the deeper he descends into the violence, the more he believes that Abbey may not know who her husband really is"--.
new book 2025 winer.
Keywords: Bourne, Jason -- (Fictitious character); Espionage; Spies; Suspense fiction; Terrorism; Novels; Thriller fiction; Spy fiction